Potential use of olive oil mill wastewater for bacterial cellulose production. Issue 3 (1st March 2022) - Sar, Taner; Yesilcimen Akbas, Meltem
ABSTRACT: In this study, olive oil mill wastewater (OOMW), an important waste in the Mediterranean basin, was evaluated to produce bacterial cellulose (BC). For this purpose, the effects of different ratios of OOMW fractions (25–100%) and some additional nutrients (yeast extract, peptone and Hestrin-Schramm medium (HS) components) on BC productions were investigated. Unsupplemented OOMW medium (75% and 100%) yielded as much as BC obtained in HS medium (0.65 g/L), while enrichment of OOMW medium (%100) with yeast extract (5 g/L) and peptone (5 g/L) increased the amount of BC by 5.5 times, reaching to 5.33 g/L. In addition, produced BCs were characterized by FT-IR, TGA, XRD and SEM analyses. BC from OOMW medium (100% OOMW with supplementation) has a high thermal decomposition temperature (316.8°C), whereas it has lower crystallinity index (57%). According to the FT-IR analysis, it was observed that the components of OOMW might be absorbed by BCs. Thus, higher yield productions of BCs from OOMW media compared to BC obtained from HS medium indicate that olive oil industry wastes can be integrated into BC production for industrial applications. Graphical Abstract: uf0001